Evaluation of the Self-help Housing Stimulant Assistance Program in Koto Kampar Hulu District, Kampar Regency - Sitri Soniati; Hasim As'ari; Nur Leila Meilani (Department of Public Administration, 2023)
This research is motivated by the fact that there are still many community houses that are classified as unfit for habitation, research and studies in the District of Koto Kampar Hulu. There are still many people who have not received the BSPS program, as evidenced by the fact that there are still many uninhabitable houses occupied by low-income people, the community has not been fully able to do self-help in building BSPS houses, the community has not been able to carry out mutual cooperation or cooperate in building BSPS houses, so community houses were abandoned during construction, and finished late. The purpose of this study was to evaluate self-help housing stimulant assistance programs. This study uses a qualitative research method with an explanatory approach. Researchers conducted data analysis based on the Reidar Dale Evaluation Main Focus concept. The research was conducted in Koto Kampar Hulu District in 2022. The results showed that the self-help housing stimulant assistance program had not been optimally implemented in Koto Kampar Hulu District. This is because the community is not fully capable of being self-supporting, it is difficult for the community to change to the old environment and conditions, and the beneficiaries are elderly, making it difficult to build houses independently.